RISET AKSI PENINGKATAN KEMAMPUAN LINGUISTIK FORENSIK BAGI PENYIDIK POLRI - Aziz, M Asrul; Suprapto, Heri (Jurnal Litbang Polri, 2022)
Crime through language is now facilitated by the presence of the internet in the digital era, for example via WhatsApp, line, SMS, Facebook, Instagram, YouTube channels, and so on. Social media of all kinds helps facilitate language crimes. Due to the existence of different media in committing crimes, namely through electronic and non-electronic media, Indonesia imposes different legal rules between the two. Facts in the field, case handling with a forensic linguistic approach is relatively rarely done optimally because of the limited ability of investigators in the field of forensic linguistics, action research is carried out by intervening in forensic linguistic knowledge to Police investigators, both with case practicum, and the application of the ELAN application method (EUDICO Linguistic). Annotator) and PRAAT, as well as AntConc software version 3.5.9 and AntWordProfiler 1.5.1. Action research was carried out at four Polda, namely the East Nusa Tenggara Regional Police, the North Sulawesi Regional Police, the East Java Regional Police and the North Sumatra Regional Police.The obstacle faced by investigators in handling legal cases that stem from the linguistic aspect is that investigators at the police stations find it difficult to find expert witnesses because there are no expert witnesses who are considered capable of in the field of forensic linguistics, the lack of support for the infrastructure to uncover language-based crimes, Inadequate ability of investigators in understanding forensic linguistics and the use of software or it related to forensic linguistics, Inadequate research budgets, especially in island areas and the inability of investigators to identify utterances or discourses that are considered a crime or use linguistic analysis to uncover cases crime Keywords: capacity building, forensic linguistics, National Police investigators